CREATION OF A POLYMER COMPOSITE WITH FUNGICIDAL PROPERTIES - KACHAN, ROMAN; ZAKOMOLDINA, ALINA; YATSUTA, INNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper proves the relevance of creating a polymer composite material in the form of varnish with fungicidal properties. Obtaining a new domestic agent in the form of a varnish will allow solving an important issue – the availability of an available domestic polymeric composite material with fungicidal properties (medical product), which can be used for the prevention and treatment of onychomycosis. In addition, this work considers the use as active substances of a new polymer composite agent with fungicidal properties of only substances that were not used in antifungal agents. This will minimize the resistance of onychomycosis pathogens to the new agent. The composition of the polymer agent was substantiated, so nitrocellulose was used as a base, which creates a layer of varnish on the surface that remains resistant to the action of water for a long time. Ethyl acetate is responsible for the speed of drying and film formation, butyl acetate for ensuring even distribution of varnish on the surface of the nail. Ethyl alcohol, which is a good solvent, was added in small concentrations to sharply reduce the explosive and flammable properties of nitrocellulose in the created composition. Ethyl alcohol is also a good preservative. To give the formed polymer flexibility, the ability to resist stretching during operation, the plasticizer triacetin, whichis an ester of glycerin and acetic acid, known as food additive E1518, was chosen. Triacetin is an excipient in the production of pharmaceutical products, where it is used as a moisturizing agent and plasticizer. an important aspect in the creation of a polymer product for the prevention and treatment of onychomycosis is the presence of substances that loosen and soften the nail plate of the nail. This will help clean the affected and dead areas from the nail, helping the diffusion of active substance to the deeper layers of the nail and its general therapy. Urea is a substance included in the WHO list of essential medicines, which contains the most effective and safe medicines. The peculiarity of urea is the small size of its molecules, thanks to which it can be an agent-conductor of the necessary substances into the deep layers of the nail.